Sericulture Mechanization Poses New Challenges for Environmental Disinfection—Evaluating the Effects of Three Newly Introduced Disinfectants - Xinyue Zhu; Jian Xiao; Yu Li; Xiaoyu Lei; Huarui Zhang; Zhaoyi Qian; Chao Sun; Yongqi Shao (AgriEngineering)
While conventional sericulture has developed effective disinfection methods, the increasing demand for silk and pupae is driving mechanization, potentially altering or introducing silkworm pathogens. New disinfection strategies are essential for sustainable sericulture production. This study first investigated the bacterial community differences between conventional and mechanized silkworm-rearing environments. Then, under the mechanized environment, we evaluated three commercially available disinfectants with different mechanisms: hypochlorous acid (HClO), nano platinum-polyhexamethylene guanide (Pt-PHMG), and medium-chain fatty acids (MCFA). Our results indicated significant bacterial differences between the two environments, with potential pathogenic bacteria present in both environments. Moreover, the bacterial communities remained relatively stable, while conventional disinfection methods were less effective in mechanized conditions. In contrast, regardless of whether they were applied before or after silkworm rearing, all three disinfectants demonstrated significant efficacy, with the total environmental bacterial load reduced by approximately 0.5 to 1 order of magnitude after application. Among them, Pt-PHMG exhibited the best performance by inhibiting pathogens such as Staphylococcus, Enterococcus, and Bacillus, followed by MCFA and HClO. The results also suggested a need for stronger disinfection strategies after silkworm rearing. These findings not only provide important hygiene practices to ensure mechanized silkworm rearing, but also offer valuable insights for the future development of disinfection strategies in modern sericulture.